Women’s Participation in Financial Decisions in Rural and Urban Haryana - Ruchi; Kumari, Vinod; Chander, Subhash; Malik, Joginder Singh; Ghalawat, Suman (Indian Journal of Extension Education, 2024)
Women the silent architects of society, weave the fabric of families and communities. Their influence extends far beyond the confines of their homes, shaping the very essence of progress.In the intricate dance of life; women’s decisions resonate powerfully in the realm of financial activities. By empowering women to actively participate in economic matters, we bridge long standing gaps and pave the way for collective growth. India, a tapestry of diversity, thrives when its women thrive. Their financial literacy becomes the compass guiding us toward prosperity and the investment not only in their well-being but also in their knowledge, is required. Keeping this in view, the study was carried out on a sample size of 256 respondents in the districts of Hisar and Kaithal during 2023. The study was on the working and non-working women of Haryana. The results showed that working and non-working women of rural area had less involvement in financial matters as compared to urban women. Among the non-working women, more than one- third of the respondents took decisions independently related to purchase of clothes, purchase of daily food articles and purchase of utensils.